ASESMENT POST TRAUMATIC STRESS DISORDER (PTSD) PADA PEREMPUAN KORBAN PERKOSAAN (ACQUAINTANCE RAPE) - Solichah, Mutingatu (HUMANITAS (Jurnal Psikologi Indonesia), 2013)
AbstractThis research was intended to find out whether Post Traumatic StressÂ Disorder (PTSD) symptom manifested in 5 women acquaintance rapeÂ survivors.PTSD Symptom was measured by the Clinician-AdministeredÂ PTSD Scale (CAPS), a semi structured interview guide that assesses 17Â clinical symptoms of PTSD outlines in DSM IV criterion along with 3Â associated features of PTSD symptoms. Quantitative data is used todetermine the categorical rating of the PTSD diagnostic status of theÂ participants (PTSD present or absent), symptom severity, and changesÂ gradations of symptom severity over time. Participants were 5 womenÂ survivors of acquaintance rape, aged 17 â 35 years old. The results show 4Â from 5 participants was diagnosed having PTSD which symptom severityÂ varied. The CAPSâ PTSD diagnostic procedure is combined between theÂ DSM IV defined 20 symptom criteria and its symptomâs frequency andÂ intensity, so the score should range from 20 the lowest up to 160. TheÂ participants score range from 35â 125, but one participant was not eligiblefor PTSD diagnostic status due to failure to meet DSM IV criterion forÂ PTSD. The interval time between the traumatic event (rape) and researchÂ was ranging from 4 to 31 years, however PTSD symptomâs severity inÂ participants remain high.Keywords: acquaintance rape, Clinician-Administered PTSD ScaleÂ (CAPS), DSM IV.